Perovskite quantum dot diffusion plate crushed material recycling method

By adding a certain proportion of crushed materials to the production of perovskite quantum dot diffusion plates and using them in combination with new materials, the problem of poor stability of diffusion plates under harsh conditions is solved, and 100% utilization rate of raw materials and low production costs are achieved.

CN119842164APending Publication Date: 2025-04-18WENZHOU XINXIN TAIJING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411840629.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Perovskite quantum dot diffusion plates are difficult to maintain good stability under harsh conditions such as humidity, oxygen environment, strong light, and thermal atmosphere. Especially after being cut or crushed, the structural integrity of the water-oxygen barrier film is destroyed and it can no longer provide effective protection for quantum dots, resulting in rapid attenuation of its luminous performance.

Method used

By adding a certain proportion of diffusion plate crushed materials to the production, the crushed materials are used with new materials to form a quantum dot luminescent layer, ensuring that the production utilization rate of raw materials reaches 100%, and reducing the production costs of enterprises.

Benefits of technology

It effectively improves the utilization rate and market competitiveness of perovskite quantum dot diffusion plates, while reducing production costs, and maintains good luminescence performance stability under high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842164A_ABST
    Figure CN119842164A_ABST
Patent Text Reader

Abstract

The invention relates to a method for recycling crushed materials of a perovskite quantum dot diffusion plate, the perovskite quantum dot diffusion plate is provided with a quantum dot light-emitting layer, the quantum dot light-emitting layer is composed of new materials and crushed materials, and the types of raw materials of the quantum dot light-emitting layer cover the types of raw materials of the crushed materials; the diffusion plate crushed material recycling method comprises the following steps: S1, determining a formula of a quantum dot light-emitting layer; S2, calculating the mass of each raw material in the crushed material; S3, calculating the mass of each raw material in a new material; and S4, manufacturing the quantum dot light-emitting layer. On the premise that the performance of the product is not affected due to qualitative change, a certain proportion of diffusion plate crushed aggregates are added in production, the crushed aggregates are matched with new materials for use, the production utilization rate of raw materials is increased to 100%, and the production cost of an enterprise is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycling and reusing perovskite quantum dots, and in particular relates to a method for recycling perovskite quantum dot diffusion plate scraps. Background Art

[0002] Compared with traditional diffusers, perovskite quantum dot diffusers have attracted the attention of many researchers in recent years due to their excellent optical properties, lower synthesis cost and environmental friendliness. However, current perovskite quantum dot materials are difficult to maintain good stability under harsh conditions such as humidity, oxygen environment, strong light and hot atmosphere.

[0003] In order to solve the problem of stability of perovskite quantum dots, the quantum dot diffusion plate is made into a "sandwich" structure by heating in-mold co-extrusion molding, the middle layer is the quantum dot layer, and the upper and lower layers are barrier films. This structure protects the quantum dots. For example, the Chinese patent with announcement number CN216670312U discloses a high-stability quantum dot diffusion plate, which includes a first upper barrier layer, a second upper barrier layer, a quantum dot layer, a second lower barrier layer and a first lower barrier layer in sequence. By providing water and oxygen barrier layers on both the upper and lower sides of the quantum dot layer, the high water resistance and high oxygen resistance of the barrier layer are utilized to improve the optical performance stability of the quantum dot diffusion plate.

[0004] After the processing of the quantum dot diffusion plate is completed, it is necessary to trim the edges so that the size of the trimmed diffusion plate fits the size of the display device, so as to facilitate assembly into the backlight module of the display device. This will result in a large amount of diffusion plate cuttings. However, when the above-mentioned diffusion plate cuttings are crushed and reused, once the diffusion plate is chopped or crushed (i.e., "diffusion plate scraps"), the structural integrity of the water and oxygen barrier film is destroyed, and it can no longer provide effective protection for the quantum dots, causing the perovskite quantum dots to be susceptible to high temperature and water and oxygen erosion. If the diffusion plate scraps are reused, they will undergo a secondary heating and in-mold co-extrusion molding process. At this time, since the structure of the water and oxygen barrier film is destroyed, the perovskite quantum dots in the diffusion plate scraps are more susceptible to environmental factors (such as secondary heating, water and oxygen invasion, etc.), thereby rapidly attenuating their luminescence performance.

[0005] With the development of technology, our company has previously applied for a Chinese patent with the publication number CN118165723A, a perovskite nanocrystal fluorescent material, which is located in the pores of the micro / mesoporous template and encapsulated by the micro / mesoporous template. The micro / mesoporous template is used as a "shell" to protect the perovskite nanocrystals to block water and oxygen. When this material is used to make quantum dot diffusion plates, expensive water and oxygen barrier films are no longer needed, and it is not easy to react with oxygen and water vapor in the air to cause its quality change and failure. Therefore, the fragments produced by the quantum dot diffusion plates produced by it may be recycled and reused, and it is expected to increase the production utilization rate of raw materials to 100%, so as to further reduce the production costs of enterprises, so it needs to be improved. Summary of the invention

[0006] The present invention proposes a method for recycling perovskite quantum dot diffusion plate scraps. Under the premise of not changing the quality of the product and affecting its performance, by adding a certain proportion of diffusion plate scraps in production, the scraps are used together with new materials, and the production utilization rate of raw materials is increased to 100%, so as to further reduce the production cost of the enterprise.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for recycling scraps of a perovskite quantum dot diffusion plate, wherein the perovskite quantum dot diffusion plate has a quantum dot light-emitting layer, the quantum dot light-emitting layer is composed of new materials and scraps, and the raw material types of the quantum dot light-emitting layer include the raw material types of the scraps;

[0009] The method for recycling the diffuser plate scraps comprises the following steps:

[0010] S1. Determine the formula of the quantum dot light-emitting layer:

[0011] The formula of the quantum dot light-emitting layer includes the following mass components:

[0012] Carrier resin A 65-96 parts;

[0013] Perovskite quantum dot masterbatch 1.5-40 parts;

[0014] Foaming agent 0.005-2 parts;

[0015] S2. Calculate the mass of each raw material in the scraps:

[0016] The amount of the crushed material added is no more than 30% of the total mass of the quantum dot light-emitting layer, so as to calculate the mass of each raw material in the crushed material, wherein: the calculated mass of the foaming agent is recorded as Y;

[0017] Construct a foaming agent residual coefficient X, where the foaming agent residual coefficient X is 0.35 - 0.65, and the actual mass of the foaming agent in the shredded material is (0.35 - 0.65)Y;

[0018] S3. Calculate the mass of each raw material in the new material:

[0019] Subtract the mass of each raw material in the shredded material from the formulated mass of each raw material in the quantum dot light-emitting layer to obtain the mass of each raw material in the new material;

[0020] S4. Fabricate the quantum dot light-emitting layer:

[0021] Blend the new material and the shredded material, and put them into an extruder to be heated and melted and extruded to obtain the quantum dot light-emitting layer.

[0022] Further, the perovskite quantum dot diffusion plate is an N-layer structure (N≥3) and one of the layers is a quantum dot light-emitting layer; light-transmitting protective layers are provided on both sides of the quantum dot light-emitting layer; a plurality of pores and a plurality of perovskite quantum dots are distributed in the quantum dot light-emitting layer.

[0023] Further, the perovskite quantum dot masterbatch is a carrier resin B loaded with perovskite quantum dots, and the carrier resin B is the same as or different from the carrier resin A.

[0024] Further, the perovskite quantum dot masterbatch includes a red masterbatch and a green masterbatch;

[0025] The red masterbatch has an ABX y X' 3-y perovskite structure, where the molar ratio of A, B, X, and X' is 1:1:y:3 - y, where 0 < y < 3, and A is Cs, B is Pb, Sn, or Cu, and X and X' are different and are each independently Cl, Br, or I;

[0026] The green masterbatch has an ABX3 perovskite structure, where the molar ratio of A, B, and X is 1:1:3, and A is Cs, B is Pb, Sn, or Cu, and X is Cl, Br, or I.

[0027] In the present invention, the metering of the red and green perovskite quantum dot masterbatches is adjusted according to the required color gamut requirements. This is a conventional technical choice for those skilled in the art and is only briefly described here.

[0028] Further, the carrier resin A is one of PC resin, PS resin, PMMA resin, and PET resin;

[0029] The carrier resin B is one of PC resin, PS resin, PMMA resin, and PET resin.

[0030] Further, the foaming agent is one or more of ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium nitrite, azodicarbonamide, azobisisobutyronitrile, diisopropyl azodicarboxylate, diethyl azodicarboxylate, N,N-dinitrosopentamethylenetetramine, N'N-dimethyl-N'N-dinitrosoterephthalamide, benzenesulfonylhydrazide, p-toluenesulfonylhydrazide, 4'4-oxidized bisbenzenesulfonylhydrazide, 1,3-disulfonylhydrazide benzene, p-toluenesulfonylamide urea, 4'4-chloro bisbenzenesulfonylamide urea, and 2,4,6-trihydrazino-1,3,5-triazine.

[0031] Further, the light-transmitting protective layer includes a carrier resin C, and the carrier resin C is consistent with the carrier resin A;

[0032] The density of the light-transmitting protective layer is greater than 1 g / cm 3 The density of the quantum dot light-emitting layer is less than 0.85 g / cm 3 The overall density of the foamed quantum dot optical diffuser is 0.90-0.95g / cm 3 .

[0033] In the present invention, the light-transmitting protective layer (higher density) covers the quantum dot light-emitting layer (lower density) to prevent the pores from breaking under external impact, thereby protecting the quantum dot light-emitting layer in the middle. The overall density of the quantum dot diffusion plate of the present application is controlled at 0.90-0.95 g / cm 3 .

[0034] Furthermore, at least one of the perovskite quantum dots forms a composite structure with the cell wall.

[0035] Furthermore, the residual coefficient X of the foaming agent in step S2 is 0.40-0.60, and the actual mass of the foaming agent in the crushed material is (0.40-0.60)Y.

[0036] Furthermore, the perovskite quantum dot diffusion plate has a three-layer structure, which includes a light-transmitting protective layer / a quantum dot light-emitting layer / a light-transmitting protective layer, and the thickness ratio of the three layers is 1.5:7:1.5;

[0037] The residual coefficient X of the blowing agent is defined as: when at least one of the perovskite quantum dots is observed to form a composite structure with the cell wall, the residual coefficient X of the blowing agent in the crushed material is partially reacted.

[0038] In the prior art, the foamed quantum dot diffusion plate usually adopts a layered structure design, such as the foamed diffusion layer and the quantum dot light-emitting layer are not located in the same layer. This is because the foaming diffusion layer will introduce a foaming agent during the preparation process, and then introduce some factors that are not conducive to the stability of quantum dots, such as bubbles, moisture, oxygen, etc. Separating the quantum dot layer from the foamed diffusion layer can effectively avoid these factors from damaging the quantum dot material. This leads to the technical prejudice that the pores and quantum dots cannot be located in the same layer.

[0039] Beneficial effects of the present invention:

[0040] (1) The diffuser plate of the present invention places the pores and the perovskite quantum dots in the same layer. At least one perovskite quantum dot forms a composite structure with the pore wall. The pores have refracting and scattering effects, which improve the uniformity and diffusion effect of light. The perovskite quantum dots are responsible for the absorption, conversion and emission of external excitation light. The composite structure formed by the two will further enhance the scattering and diffusion effect of light. Due to the small size effect of quantum dots, they can generate more scattering centers inside the pores, making the propagation path of light in the diffuser plate more complex and diverse, thereby helping to achieve a more uniform light distribution.

[0041] (2) During the extrusion molding process of the diffusion plate of the present invention in the heating mold, the foaming agent will decompose and produce gas when heated, and bubbles will be formed in the quantum dot light-emitting layer. In order to form a composite structure between the bubbles and the perovskite quantum dots, the foaming agent will be added in excess so that it cannot react completely, resulting in part of the foaming agent remaining in the diffusion plate, thereby extending the foaming agent residual remainder coefficient X. At this time, the residual foaming agent in the scraps can still play a role, and at least one of the perovskite quantum dots in the cross section of the diffusion plate is observed to form a composite structure with the bubble wall, and the residual remainder coefficient X of the foaming agent in the scraps that is partially reacted is established.

[0042] (3) The present invention adds the scraps (edge ​​materials, adjustment materials, punching materials, etc. produced by the quantum dot diffusion plate) to the new materials in a certain proportion for use, which will not cause the product to change in quality and affect its performance. It effectively improves the utilization rate, greatly reduces the production cost, and improves its market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the product structure of the quantum dot diffusion plate of the present invention.

[0044] Figure numerals: 1. light-transmitting protective layer; 2. quantum dot light-emitting layer; 3. carrier resin A; 4. pores; 5. perovskite quantum dots. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described here are only used to explain the present invention and are not used to limit the present invention.

[0046] A perovskite quantum dot diffusion plate has a three-layer structure of a light-transmitting protective layer / a quantum dot luminescent layer / a light-transmitting protective layer, and the thickness ratio of the three layers is 1.5:7:1.5. A plurality of pores and a plurality of perovskite quantum dots are distributed in the quantum dot luminescent layer, and at least one of the perovskite quantum dots forms a composite structure with the pore wall.

[0047] The density of the light-transmitting protective layer is greater than 1 g / cm 3 The density of the quantum dot light-emitting layer is less than 0.85 g / cm 3 The overall density of the foamed quantum dot optical diffuser is 0.90-0.95g / cm 3 .

[0048] Embodiment 1:

[0049] A method for recycling perovskite quantum dot diffusion plate scraps comprises the following steps:

[0050] S1. Determine the formula of the quantum dot light-emitting layer and the light-transmitting protective layer to be produced:

[0051]

[0052]

[0053] Table 1: Formula of quantum dot light-emitting layer and light-transmitting protective layer

[0054] In the above, the diffusion masterbatch is one or more of titanium dioxide, silicon dioxide, calcium sulfate, barium sulfate, zinc oxide, silicone, and PS microspheres; preferably, titanium dioxide is selected in this embodiment.

[0055] In the above, the foaming agent is one or more of ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium nitrite, azodicarbonamide, azobisisobutyronitrile, diisopropyl azodicarboxylate, diethyl azodicarboxylate, N,N-dinitrosopentamethylenetetramine, N'N-dimethyl-N'N dinitrosoterephthalamide, benzenesulfonylhydrazide, p-toluenesulfonylhydrazide, 4'4-oxidized bisbenzenesulfonylhydrazide, 1,3-disulfonylhydrazide benzene, p-toluenesulfonylamide urea, 4'4-chloro bisbenzenesulfonylamide urea, 2,4,6-trihydrazine-1,3,5-triazine. Preferably, ammonium carbonate is selected in this embodiment.

[0056] In the above, the red masterbatch of perovskite quantum dots is PS loaded with red perovskite quantum dots; and the green masterbatch of perovskite quantum dots is PS loaded with red perovskite quantum dots.

[0057] According to the process requirements, the thickness of the light-transmitting protective layer is 30% of the product thickness, and the quantum dot luminous layer in the middle accounts for 70%. For example, for a 1mm thick diffusion plate, the upper and lower wrapping layers are 0.15mm each, and the middle layer is 0.7mm.

[0058] S2. Calculate the mass of each raw material in the scraps:

[0059] The amount of crushed material added is 30% of the total mass of the quantum dot light-emitting layer, and 120kg*30%=36kg of crushed material is required.

[0060] According to the ratio of quantum dot light-emitting layer to light-transmitting protective layer of 7:3, it was found that the crushed material contained 25.2kg of quantum dot light-emitting layer and 10.8kg of light-transmitting protective layer.

[0061] To calculate the mass of each raw material in the crushed material, see Table 2 for details.

[0062]

[0063] Table 2: Mass of each raw material component in the crushed material

[0064] The residual coefficient X of the foaming agent is constructed, and the residual coefficient X of the foaming agent is 0.35-0.65. Since the residual coefficient X of different foaming agents is different, the residual coefficient X of ammonium carbonate used in this embodiment 1 is 0.55. At this time, the actual mass of the foaming agent in the crushed material is 0.55*0.29kg=0.16kg.

[0065] S3. Calculate the mass of each raw material in the new material:

[0066] The mass of each raw material in the new material can be obtained by subtracting the mass of each raw material in the crushed material from the mass of each raw material in the quantum dot light-emitting layer.

[0067] At this time, the amounts of the raw materials for the quantum dot light-emitting layer in the new material are detailed in Table 3.

[0068]

[0069] Table 3: Amount of each raw material used in the quantum dot light-emitting layer of the new material

[0070] Since the light-transmitting protective layer of the quantum dot diffusion plate does not contain any debris, it remains unchanged.

[0071] S4. Making quantum dot diffusion plate:

[0072] The components of the light-transmitting protective layer (see the right side of Table 1) are split into two parts and put into two independent lower hoppers respectively; the new material calculated in step S3 (Table 3) and the crushed material calculated in step 2 (Table 2) are blended and added to the independent lower hopper in the middle. The blending and extrusion are carried out by a twin-screw extruder at an extrusion temperature of 210-240°C, and after traction cooling, a sandwich-structured foamed quantum dot diffusion plate is obtained.

[0073] The method for determining whether at least one of the perovskite quantum dots and the cell wall forms a composite structure is as follows: Figure 1 , cut the produced quantum dot diffusion plate into several small plates, the number of which is ≥ 2. And observe whether there are convex particles on the inner wall of the pores of several small plate sections. Sample the convex particles on the inner wall of the pores and perform XRD identification.

[0074] The multi-layer co-extrusion (heating and melting extrusion by extruder) preparation method of the diffusion plate of the present invention is a prior art and will not be described in detail here. Please refer to the Chinese patent publication number CN116769259A which discloses a foamed quantum dot diffusion plate.

[0075] Comparative Example 1:

[0076] The difference from Example 1 is that no crushed material is added.

[0077] According to the formula of the quantum dot light-emitting layer and the light-transmitting protective layer in step S1, the quantum dot diffusion plate is directly prepared, that is, there is no process of step S2 and step S3 as in Example 1, so as to obtain the product.

[0078] Comparative Example 2:

[0079] The difference from Example 1 is that the amount of crushed material added to the quantum dot light-emitting layer is increased to 50%, and the product is obtained. When the prepared diffuser plate is laid flat, one edge in the width direction has obviously separated from the platform due to warping, and is prone to yellowing, and the product quality is unqualified.

[0080] Experimental analysis:

[0081] 1. Brightness test: Use a handheld spectrometer to measure the brightness value before and after long-term aging, and calculate the brightness attenuation rate. When the brightness attenuation rate is not higher than 30%, it can meet the use requirements.

[0082] Long-term aging test conditions: The diffuser plate samples were aged for 1000 hours at 85°C and 85% RH.

[0083] 2. Color gamut test: Adopt NTSC standard color gamut test method, select wavelength of blue light source of backlight as 450-480nm, and select total LED power as 35w; measure color gamut value before and after long-term aging, and calculate color gamut attenuation rate. When color gamut attenuation rate is not higher than 30%, it can meet the use requirements.

[0084] The test was carried out according to the above test method. The test results are shown in Table 4 below:

[0085]

[0086] It can be seen that the brightness attenuation rate and color gamut attenuation rate of the diffusion plate product with added crushed materials in the present invention before and after the high temperature and high humidity aging test are not significantly different from those of the control group, and the product meets the national test standards through tests such as anti-yellowing, warping, and impact resistance. The crushed materials of all perovskite quantum dot diffusion plates can be formulated and reused using this calculation method. Under the premise of the inventive concept provided by the present invention, those skilled in the art can complete the precise conversion of the formula of each product model. Thereby effectively and reasonably utilizing resources, greatly reducing production costs, and improving market competitiveness.

[0087] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for recycling scraps of perovskite quantum dot diffusion plates, characterized in that: The perovskite quantum dot diffusion plate has a quantum dot light-emitting layer, the quantum dot light-emitting layer is composed of new materials and crushed materials, and the raw material types of the quantum dot light-emitting layer include the raw material types of the crushed materials; The method for recycling the diffuser plate scraps comprises the following steps: S1. Determine the formula of the quantum dot light-emitting layer: The formula of the quantum dot light-emitting layer includes the following mass components: 65-96 parts of carrier resin A; Perovskite quantum dot masterbatch 1.5-40 parts; Foaming agent 0.005-2 parts; S2. Calculate the mass of each raw material in the scraps: The amount of the crushed material added is no more than 30% of the total mass of the quantum dot light-emitting layer, so as to calculate the mass of each raw material in the crushed material, wherein: the calculated mass of the foaming agent is recorded as Y; Constructing a foaming agent residual coefficient X, wherein the foaming agent residual coefficient X is 0.35-0.65, and the actual mass of the foaming agent in the crushed material is (0.35-0.65)Y; S3. Calculate the mass of each raw material in the new material: The mass of each raw material in the new material can be obtained by subtracting the mass of each raw material in the crushed material from the mass of each raw material in the quantum dot light-emitting layer. S4. Making quantum dot light-emitting layer: The new material and the scrap material are mixed and put into an extruder for heating, melting and extrusion to obtain a quantum dot light-emitting layer.

2. The method for recycling perovskite quantum dot diffusion plate scraps according to claim 1, characterized in that: The perovskite quantum dot diffusion plate is an N-layer structure (N≥3) and one layer is a quantum dot light-emitting layer, and both sides of the quantum dot light-emitting layer are provided with a light-transmitting protective layer; a plurality of pores and a plurality of perovskite quantum dots are distributed in the quantum dot light-emitting layer.

3. The method for recycling the scraps of perovskite quantum dot diffusion plates according to claim 1, characterized in that: The perovskite quantum dot masterbatch is a carrier resin B loaded with perovskite quantum dots, and the carrier resin B and the carrier resin A are made of the same or different materials.

4. The method for recycling the scraps of perovskite quantum dot diffusion plates according to claim 3, characterized in that: The perovskite quantum dot masterbatch includes a red masterbatch and a green masterbatch; The red masterbatch has ABX y X' 3-y a perovskite structure, wherein the molar ratio of A, B, X, and X' is 1:1:y:3-y, where 0 < y < 3, A is Cs, B is Pb, Sn, or Cu, X and X' are different and are each independently Cl, Br, or I; The green masterbatch has an ABX3 perovskite structure, wherein the molar ratio of A, B and X is 1:1:3, and A is Cs, B is Pb, Sn or Cu, and X is Cl, Br or I.

5. The method for recycling the scraps of perovskite quantum dot diffusion plates according to claim 3, characterized in that: The carrier resin A is one of PC resin, PS resin, PMMA resin and PET resin; The carrier resin B is one of PC resin, PS resin, PMMA resin and PET resin.

6. The method for recycling scraps of perovskite quantum dot diffusion plates according to claim 1, characterized in that: The foaming agent is one or more of ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, ammonium nitrite, azodicarbonamide, azobisisobutyronitrile, diisopropyl azodicarboxylate, diethyl azodicarboxylate, N,N-dinitrosopentamethylenetetramine, N'N-dimethyl-N'N-dinitrosoterephthalamide, benzenesulfonylhydrazide, p-toluenesulfonylhydrazide, 4'4-oxidized bisbenzenesulfonylhydrazide, 1,3-disulfonylhydrazide benzene, p-toluenesulfonylamide urea, 4'4-chloro bisbenzenesulfonylamide urea, and 2,4,6-trihydrazino-1,3,5-triazine.

7. The method for recycling the scraps of perovskite quantum dot diffusion plates according to claim 2, characterized in that: The light-transmitting protective layer includes a carrier resin C, and the carrier resin C is consistent with the carrier resin A; The density of the light-transmitting protective layer is greater than 1 g / cm 3 The density of the quantum dot light-emitting layer is less than 0.85 g / cm 3 .

8. The method for recycling scraps of perovskite quantum dot diffusion plates according to claim 2, characterized in that: At least one of the perovskite quantum dots forms a composite structure with the cell wall.

9. The method for recycling scraps of perovskite quantum dot diffusion plates according to claim 8, characterized in that: The residual coefficient X of the foaming agent in step S2 is 0.40-0.60, and the actual mass of the foaming agent in the crushed material is (0.40-0.60)Y.

10. The method for recycling scraps of perovskite quantum dot diffusion plates according to claim 9, characterized in that: The perovskite quantum dot diffusion plate has a three-layer structure, which includes a light-transmitting protective layer / a quantum dot light-emitting layer / a light-transmitting protective layer, and the thickness ratio of the three layers is 1.5:7:1.5; The residual coefficient X of the blowing agent is defined as: at least one of the perovskite quantum dots forms a composite structure with the cell wall, and at this time, the residual coefficient X of the blowing agent in the crushed material is partially reacted.

Citation Information

Patent Citations

  • Foaming quantum dot optical diffusion plate

    CN116769259A

  • Perovskite nanocrystalline fluorescent material and preparation method and application thereof

    CN118165723A

  • High-stability quantum dot diffusion plate

    CN216670312U